Prognostic relevance of clinical and molecular risk factors in children with high-risk medulloblastoma treated in the phase II trial PNET HR+5. Issue 7 (30th December 2020) - Dufour, Christelle; Foulon, Stephanie; Geoffray, Anne; Masliah-Planchon, Julien; Figarella-Branger, Dominique; Bernier-Chastagner, Valerie; Padovani, Laetitia; Guerrini-Rousseau, Léa; Faure-Conter, Cecile; Icher, Celine; Bertozzi, Anne-Isabelle; Leblond, Pierre; et al.
Abstract: Background: High-risk medulloblastoma is defined by the presence of metastatic disease and/or incomplete resection and/or unfavorable histopathology and/or tumors with MYC amplification. We aimed to assess the 3-year progression-free survival (PFS) and define the molecular characteristics associated with PFS in patients aged 5–19 years with newly diagnosed high-risk medulloblastoma treated according to the phase II trial PNET HR+5. Methods: All children received postoperative induction chemotherapy (etoposide and carboplatin), followed by 2 high-dose thiotepa courses (600 mg/m 2 ) with hematological stem cell support. At the latest 45 days after the last stem cell rescue, patients received risk-adapted craniospinal radiation therapy. Maintenance treatment with temozolomide was planned to start between 1–3 months after the end of radiotherapy. The primary endpoint was PFS. Outcome and safety analyses were per protocol (all patients who received at least one dose of induction chemotherapy). Results: Fifty-one patients (median age, 8 y; range, 5–19) were enrolled. The median follow-up was 7.1 years (range: 3.4–9.0). The 3 and 5-year PFS with their 95% confidence intervals (95% CI) were 78% (65–88) and 76% (63–86), and the 3 and 5-year OS were 84% (72–92) and 76% (63–86), respectively. Medulloblastoma subtype was a statistically significant prognostic factor ( P -value = 0.039) with large-cell/anaplastic being of worse prognosis, as well as a molecular subgroup ( P -value = 0.012) with sonic hedgehog (SHH) and group 3 being of worse prognosis than wingless (WNT) and group 4. Therapy was well tolerated. Conclusions: This treatment based on high-dose chemotherapy and conventional radiotherapy resulted in a high survival rate in children with newly diagnosed high-risk medulloblastoma.